Fast Decision of Block Size, Prediction Mode, and Intra Block for H.264 Intra Prediction - Yi-Hsin Huang; Tao-Sheng Ou; Chen, H H (IEEE transactions on circuits and systems for video technology, 2010)
The spatial-domain intra prediction scheme of H.264 has high computational complexity, especially for the High Profile as it incorporates the additional intra 8 × 8 prediction mode. To address this issue, we explore the hierarchy of H.264 mode decision process in this paper and adopt an approach that is in synchrony with the mode decision hierarchy. In particular, we propose a variance-based algorithm for block size decision, an improved filter-based algorithm for prediction mode decision using contextual information, and a selection algorithm for intra block decision that exploits the relation between the rate-distortion characteristic and the best coding type. Performance comparison is provided to show the improvement of the proposed algorithms over previous methods.